Proposals (23–25): to conserve the names Galio-Carpinetum Oberdorfer 1957, Lithospermo-Carpinetum Oberdorfer 1957 and Stellario-Carpinetum Oberdorfer 1957 - Novák, Pavel (Phytocoenologia, 2019)
(23) Galio sylvatici-Carpinetum betuli Oberdorfer 1957: 424–435. Typus: Oberdorfer (1952), Table 2, rel. 86a (lectotypus Willner & Grabherr 2007: 232). (=) Querco pedunculatae-Carpinetum betuli Klika 1928: 34–37. Typus: Klika (1928), Table on pp. 35–37, rel. 1 (lectotypus hoc loco). (24) Lithospermo-Carpinetum betuli Oberdorfer 1957: 440–442. Typus: Issler (1926), Table 3, rel. 2 (typus cons. propos.). (=) Carpinetum betuli Issler 1925: 276–279. Typus: Issler (1925), rel. on pp. 278–279 (lectotypus hoc loco). (25) Stellario holostei-Carpinetum betuli Oberdorfer 1957: 419–424. Typus: see below. (=) Alno glutinosae-Carpinetum betuli Issler 1926: 18–20, 22–25. Typus: Issler 1926, Table 2, rel. 6 (lectotypus hoc loco).